2009
DOI: 10.1109/tbme.2008.2003293
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Identifying Locomotion Modes Using Surface Electromyography

Abstract: This study investigated the use of surface electromyography (EMG) combined with pattern recognition (PR) to identify user locomotion modes. Due to the nonstationary characteristics of leg EMG signals during locomotion, a new phase-dependent EMG PR strategy was proposed for classifying the user's locomotion modes. The variables of the system were studied for accurate classification and timely system response. The developed PR system was tested on EMG data collected from eight able-bodied subjects and two subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
334
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(343 citation statements)
references
References 26 publications
6
334
2
1
Order By: Relevance
“…An adaptive algorithm, based on decision trees and four sensors attached to the human body, was implemented for recognition of daily activities such as walking, standing and sitting with an accuracy of 99% [16]. Fusion of a linear discriminant analysis (LDA) method and a two-layered artificial neural network (ANN), was used for identification of locomotion modes with twelve surface EMG signals [17]. LDA and ANN methods have also been used with time-domain and frequency-domain features from nine EMG signals for intent recognition [18], [19].…”
Section: Related Workmentioning
confidence: 99%
“…An adaptive algorithm, based on decision trees and four sensors attached to the human body, was implemented for recognition of daily activities such as walking, standing and sitting with an accuracy of 99% [16]. Fusion of a linear discriminant analysis (LDA) method and a two-layered artificial neural network (ANN), was used for identification of locomotion modes with twelve surface EMG signals [17]. LDA and ANN methods have also been used with time-domain and frequency-domain features from nine EMG signals for intent recognition [18], [19].…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, large progress has been observed in wearable sensors -for instance, lightweight and fast inertial measurement units (IMUs) and soft kinematic sensors [6], [7], [8]. In contrast, the deployment of computational methods that permit to perform fast and accurate human motion analysis, recognition of walking activities and prediction of gait events are still under development [9], [10], [11]. In this work, we present a novel strategy for recognition and prediction of gait events, that combines two computational intelligence approaches: Adaptive Neuro-Fuzzy and Bayesian methods (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…High classification accuracies can be achieved by this approach, however; it requires an extensive collection of data for training the classifier [4]. The main challenge in the powered devices is the lack of direct control by amputees [5]. Therefore, the need to control the prostheses intuitively has brought the ideas of using surface electromyography (sEMG), mechanical sensors or a fusion-based control.…”
Section: Introductionmentioning
confidence: 99%
“…Surface EMG (sEMG) electrodes have been used to record muscle activities signals from amputees wearing passive prostheses and powered prostheses [6]. Several studies investigated EMG PR to identify the user intent in different activities [5,7,8] for smooth, intuitive and natural control of prostheses. A number of studies have reported the use of mechanical sensors (inertial measurement units (IMUs)), load sensors and pressure-sensitive insoles) for lower limb activity recognition [6,9,10].…”
Section: Introductionmentioning
confidence: 99%